Analisis Strategi Bisnis PT Gudang Garam Tbk dalam Industri Rokok Indonesia - Kevin Danendra Budianto (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to develop a suitable business strategy for PT Gudang Garam Tbk in the face of the intensifying competition within the cigarette industry. Employing a qualitative research design, the study utilized documentation analysis as the primary data collection method. The data was sourced from the Annual Report of PT Gudang Garam Tbk. The results, analyzed using the Quantitative Strategic Planning Matrix (QSPM), suggest that a market penetration strategy is the most effective strategic alternative for the company. By leveraging its internal strengths, such as a wide distribution network, strong brand loyalty, and a diverse product range, PT Gudang Garam Tbk can strengthen its competitive position in the tobacco sector. Additionally, the company can capitalize on external opportunities, including changing consumer preferences and Indonesia's large productive-age population, to enhance its brand awareness and increase market share. This approach will allow PT Gudang Garam Tbk to remain competitive and sustain its market leadership in the evolving tobacco industry landscape.